Losing the field : a field party novel - Glines, Abbi (New York : Simon Pulse, an imprint of Simon & Schuster Children's Publishing Division, 2018)
Told in separate voices, seventeen-year-old Tallulah Leddel, overweight, insecure, and angry at being ridiculed by football star Nash, and Nash, lost and bitter after an accident, unexpectedly find themselves falling in love.
Overweight and insecure, Tallulah Liddell had always been defined by her appearance. The only boy who did seem to notice her was her longtime crush, Nash Lee. When he laughs at a joke aimed at Tallulah the summer before their senior year, Tallulah becomes determined to lose weight. Nash, the star running back of Lawton's football team, is being scouted by division one colleges. An accident leaves him with a permanent limp, and he becomes bitter and angry. Tallulah and Nash unexpectedly find themselves falling for each other, but there's a complication: a teacher, Mr. Dace, is infatuated with Tallulah, too.-- adapted from jacket and perusal of book
Sequel to: After the game.
young adult fiction
Keywords: Emotions -- Juvenile fiction; Bullying -- Juvenile fiction; Overweight persons -- Juvenile fiction; Romance fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Emotional problems -- Fiction; Overweight persons -- Fiction; Love -- Fiction; High schools -- Fiction; Schools -- Fiction; Teacher-student relationships -- Fiction; Teenagers -- Sexual behavior -- Fiction; Alabama -- Fiction; Football players -- Fiction; High school students -- Fiction; Bullying; Emotions; Football players; High school students; High schools; Overweight persons; Romance fiction; Schools; Teacher-student relationships; Teenagers -- Sexual behavior; Alabama; YOUNG ADULT FICTION / Family; YOUNG ADULT FICTION / Social Themes / Emotions & Feelings; YOUNG ADULT FICTION / Sports & Recreation / Football; Fiction; Young adult fiction; Fiction; Juvenile works; Young adult works